Procesos decisorios y acciones en el sistema regional de responsabilidad social para el desarrollo del Valle del Cauca (2017)
The Regional System of Social Responsibility for Development of Valle del Cauca, SRRS, was conceived as an emergent process of co-responsibility, to promote the regionïs development. This study seeks to examine transformations of SRRS processes between the years 2006 and 2015 and how these transformations influenced the system actions and its members. Through semi-structured interviews and documents review, the analysis was focus on four critical junctures of the SRRS, describing in particular actors interactions in the governance process, the types of undertaken actions and the extent of impacts as an alliance for sustainable human development . Finally, some recommendations on the processes of co-responsibility in the Valle del Cauca context were emphasized.